Akuntansi Syariah dan Konvensional Pertarungan Paradigma antara Profit dan Prinsip - A. M. Rahmat Ramadhani Al Kautsar M.; Rahmat Hidayat; Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the paradigmatic tension between Islamic accounting and conventional accounting, focusing on the contest between profit orientation and normative principles in financial reporting. Using a qualitative literature-based approach, the research analyzes academic studies, accounting standards, and empirical findings related to IFRS and AAOIFI. The findings indicate that the divergence between Islamic and conventional accounting is rooted in fundamentally different philosophical foundations regarding accountability, value creation, and the purpose of financial information. While conventional accounting prioritizes economic efficiency and shareholder interests, Islamic accounting emphasizes ethical responsibility, shariah compliance, and social accountability. The study further reveals that the implementation of Islamic accounting faces structural challenges due to the dominance of global standards, resulting in practical compromises in disclosure, governance, and reporting behavior. However, empirical evidence suggests that shariah-based standards contribute to lower earnings management, stronger governance, and broader social reporting. The paper argues that the future of Islamic accounting depends on its ability to reconstruct a coherent paradigm that integrates economic performance with normative values, supported by strong governance and adaptive institutional frameworks